Development of an order system with a communication module - ROSTAM, HENRIK (My University, 2011)
Web development has grown rapidly since the invention of the internet so more languages and frameworks are being developed for this platform. Unfortunately, many existing systems are either expensive or not user-friendly and difficult to modify in order to satisfy different requirements. This thesis is about is about overcoming these problems and creating a modular, dynamic, reliable and secure web order system with a communication module. The system should also be easy to use both for the customer and the staff who administer it. I choose to implement this system using the PHP framework Symfony which is built up from the MVC model, together with the Object-relational mapping named Propel.
Keywords: Informations- och kommunikationsteknik; Programvaruteknik; Information & Communication Technology; Software Engineering